Clinical Utility of a Modified qRT-PCR for Trypanosoma Cruzi Detection in Transplant Patients. (July 2018) - Bonisconti, Florencia; Sanchez, Ariel German; Mas, Luciana Anahi; De la Fuente, Jorge Luis; Maraschio, Martin; Balderramo, Domingo; De Arteaga, Javier; Caeiro, Juan Pablo; Alvarellos, Teresita
Abstract : Introduction: Chagas' disease (CD) is an endemic infection caused by the protozoan Trypanosoma cruzi (TC). Due to the increased demand in solid organ transplant (SOT) waiting list, donor with CD have been considered. Reactivation (kidney 8.3%-17%1, liver 19%-33%2, heart 20%-90%3) and de novo CD infection in SOT recipients have been reported. WHO recommend two positive serological methods for CD pre-transplant (pre-tx) diagnosis. Nevertheless, these methods have a limitation in SOT patients. Molecular techniques as polymerase chain reaction (PCR) can be used independently of the host immune4 status allowing the parasite detection even before the appearance of symptoms. Our goal was monitoring SOT recipients with CD by a novel modified quantitative real-time PCR (qRT-PCR). Patients and Methods: Twenty-Five adult patients, SOT recipient [10 kidney (K), 9 liver (L), 3 liver-kidney (LK), 3 kidney-pancreas (KP)] with positive serology for CD in recipient or donor (20R+/5D+) and post-tx follow-up of parasitic load performed by qRT-PCR, were included. Immunosuppression scheme consisted in Tacrolimus (n=25), Mycophenolate (n=20) or Azathioprine (n=4), Prednisone (n=25) and Basiliximab (n=11). qRT-PCR was carried out in blood samples according to scheduled times. Benznidazole treatment was administered during 60 days in patients with positive parasitemia. Results: Follow-up time was at least 3 months. Nine patients (36%) had reactivation [6/10K (60%), 1/9L (11%), 1/3LK (33%), 1/3KP (33%)] and 1 de novo infection [1/10K (10%)] before 4 months post-tx, 8 patients with mycophenolate and 2 under azathioprine scheme. Patients with evidence of parasite load received benznidazole. Parasitic load became negative without clinical manifestation. Only 2 patients presented a second reactivation at 8 and 12 months after the first episode, due to immunosuppression adjustment. Conclusion: Early detection of parasitemia through molecular techniques as this novel qRT-PCR could assist in the control of immunocompromised patients with Chagas reactivation and de novo infection. Preemptive therapy of Chagas disease should be accomplished. Bibliography: 1.Lattes R., Lasala M.B. "Chagas disease in the immunosuppressed patient". Clin Microbiol Infect. 2014; 29:300-309. 2.Balderramo D. et al. "Chagas disease and liver transplantation: Experience in Argentina using real-time quantitative PCR for early detection and treatment". TID 2017. Doi 10.1111/tid.12782. 3.Bestetti R. et al. "A systematic review of studies oh heart transplantation for patients with end-stage Chagas' heart disease". J Cardiac Fail 2009;15:249-255. 4.Maldonado C, et al. "Using polymerase chain reaction in early diagnosis of re-activated Trypanosoma cruzi infection after heart transplantation". J Heart Lung Transplant 2004;23:1345-8